Analisis Penerapan Batas Maksimum Kepemilikan Tanah Terhadap Luas Tanah Pertanian (Studi Kasus Pada Kantor Pertanahan Kabupaten Lampung Selatan) - Noviasih Muharam (KEADILAN PROGRESIF, 2015)
Soil limited number can not be increased then in terms of land ownership can not exceed the maximum limit of agricultural land, especially land ownership. Problems in this paper, how the application of the maximum limit land ownership to extensive farming. Method of approach is normative juridical approach, data source is secondary data. The collection of data carried out the study of literature and analyzed qualitatively. The results showed that the maximum limit land ownership to agricultural land area is not in accordance with the legislation in force .. It should, the Government called on the public to inventory owned land as well as reporting so that the Government may determine ground objects that will be the object of reform.